2021
DOI: 10.2196/25160
|View full text |Cite
|
Sign up to set email alerts
|

User Perspectives of Diet-Tracking Apps: Reviews Content Analysis and Topic Modeling

Abstract: Background The availability and use of mobile apps in health and nutrition management are increasing. Ease of access and user friendliness make diet-tracking apps an important ally in their users’ efforts to lose and manage weight. To foster motivation for long-term use and to achieve goals, it is necessary to better understand users’ opinions and needs for dietary self-monitoring. Objective The aim of this study was to identify the key topics and issue… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 50 publications
0
18
0
Order By: Relevance
“…Linked to this, when discussing competing in the leagues and a personal target, it can be seen that a negative health status or having an accident were considered to be significant barriers by some participants. Equivalent concerns have been found related to diet tracking apps [ 39 ], “Well, I’m trying to…my aim is still to try and get my 60 min of exercise in a day which I’ve not been managing because I had quite a significant accident, so I wasn’t able to for a while but I’m now beginning to get that back up.” (PI4, Doris)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Linked to this, when discussing competing in the leagues and a personal target, it can be seen that a negative health status or having an accident were considered to be significant barriers by some participants. Equivalent concerns have been found related to diet tracking apps [ 39 ], “Well, I’m trying to…my aim is still to try and get my 60 min of exercise in a day which I’ve not been managing because I had quite a significant accident, so I wasn’t able to for a while but I’m now beginning to get that back up.” (PI4, Doris)…”
Section: Resultsmentioning
confidence: 99%
“…Linked to this, when discussing competing in the leagues and a personal target, it can be seen that a negative health status or having an accident were considered to be significant barriers by some participants. Equivalent concerns have been found related to diet tracking apps [39],…”
Section: Barriers To Fan Fitnessmentioning
confidence: 99%
“…Thus, the conclusions obtained may be more objective with less bias. Studies have analyzed user reviews of weight loss and precision nutrition apps [ 19 , 20 ]; however, research on mHealth sleep apps is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The recording of diet with mobile technology offers a unique opportunity to capture information that is not being recorded using traditional methods, such as the quality of food being consumed 17 . It has been reported that user satisfaction was high for dietary assessment applications, with the majority of participants preferring mobile phone dietary assessment methods to conventional methods as they provide real-time feedback on energy and nutrient intake [18][19][20] . These applications are likely to evolve and develop further in the future; with healthcare, linking to devices with biological information 21 .…”
Section: Introductionmentioning
confidence: 99%